Karyotype Differences Between Acacia seyal var. seyal and var. fistula Natural Populations in Northeastern Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
Differences in chromosome number and morphology in Acaciaseyal var. seyal and var. fistula from natural populations in Algadarif State –Sudan were investigated. Seeds of the two varieties were germinated underlaboratory conditions. Root tips were harvested, prepared and examinedunder microscope for somatic chromosomes number and morphology. Theresults showed differences in ploidy level and chromosomal morphologybetween the two varieties. The chromosome number of var. seyal was2n=4x=52, and for var. fistula was 2n=8x=104. Total chromosome lengths ofvar. seyal ranged from 2.68 μm to 5.60 μm, and from 2.15 μm to 6.71 μm forvar. fistula. The haploid chromosomes set of var. seyal were classified as 4medians, 11 sub-median and 11 slightly sub- median. For var. fistula were17 medians, 17 sub-median and 18 slightly sub- median. The higherpolyploidy level of var. fistula may indicate that var. seyal was its progenitor
Keywords: Acacia seyal; chromosome number; chromosome morphology; polyploidy, progenitor